Purging in auto- and allografts: monoclonal antibodies which use human complement and other natural effector mechanisms. - Cobbold, S; Hale, G; Clark, MR; Waldmann, H (1990)
CAMPATH-1M is a rat IgM monoclonal antibody which binds to an antigen on all human lymphocytes and monocytes, but which is not present on marrow stem cells (Hale et al., 1983). Lymphocytes can be efficiently killed in bone marrow buffy coat preparations using the antibody and donor human serum as a means to avoid graft versus host disease (GVHD) (Waldmann et al., 1984). An analysis of 520 matched sibling bone marrow transplants (BMT) for leukaemia demonstrates that T-cell depletion using CAMPATH-1M markedly reduces the incidence and severity of GVHD, but there is an increased risk of graft rejection. In the case of CGL in chronic phase, there is also an associated extra risk of relapse, particularly in patients where engraftment may have been compromised (Hale et al., 1988a). A rat IgG2b antibody of the same specificity as CAMPATH-1 (CAMPATH-1G) was developed which is able to both fix human complement and opsonize lymphocytes in vivo (Dyer et al., 1989). Initial studies for the prophylaxis of bone marrow rejection in 55 mismatched and matched unrelated donor (MUD) BMTs suggest that CAMPATH-1G treatment of the recipient may reduce, but not eliminate, marrow graft rejection. The broad CAMPATH-1 specificity means that it is also ideal for purging a range of lymphoid malignancies prior to autologous BMT, or even for direct serotherapy of leukaemic patients. However, there may be limitations of monoclonal antibody purging using complement or other natural effector mechanisms either in vivo or in vitro; in particular, antigenic modulation and an antiglobulin response. Phase 1 studies of "in vivo purging" with a monovalent CD3 antibody (Clark et al., 1989), and also with a genetically engineered humanized IgG1 (CAMPATH-1H) (Hale et al., 1988b) suggest that these limitations can be overcome.